Resprouting trees drive understory vegetation dynamics following logging in a temperate forest - Matula, Radim; Řepka, Radomír; Šebesta, Jan; Pettit, Joseph L; Chamagne, Juliette; Šrámek, Martin; Horgan, Katherine; Maděra, Petr (Scientific reports, 2020)
Removal of canopy trees by logging causes shifts in herbaceous diversity and increases invasibility of the forest understory. However, disturbed (cut) trees of many species do not die but resprout from remaining parts. Because sprouts develop vigorously immediately after disturbances, we hypothesized that sprouts of logged trees offset the changes in species richness and invasibility of the herbaceous layer by eliminating the rise in the resource availability during the time before regeneration from seeds develops. To test this, we analyzed data on herbaceous vegetation and sprout biomass collected in a broadleaved temperate forest in the Czech Republic before and for 6 years after logging. Sprouts that were produced by most of the stumps of logged trees offset large rises in species richness and cover of herbaceous plants and the resource availability that followed logging, but they affected the alien plants more significantly than the native plants. The sprouting canopy effectually eliminated most of the alien species that colonized the forest following a logging event. These findings indicate that in forests dominated by tree species with resprouting ability, sprouts drive the early post-disturbance dynamics of the herbaceous layer. By offsetting the post-disturbance vegetation shifts, resprouting supports forest resilience.